Expression profiling of 11beta-hydroxysteroid dehydrogenase type-1 and glucocorticoid-target genes in subcutaneous and omental human preadipocytes. - Bujalska, I; Quinkler, M; Tomlinson, J; Montague, C; Smith, D; Stewart, P (2006)
Obesity is associated with increased morbidity and mortality from cardiovascular disease, diabetes and cancer. Although obesity is a multi-factorial heterogeneous condition, fat accumulation in visceral depots is most highly associated with these risks. Pathological glucocorticoid excess (i.e. in Cushing's syndrome) is a recognised, reversible cause of visceral fat accumulation. The aim of this study was to identify depot-specific glucocorticoid-target genes in adipocyte precursor cells (preadipocytes) using Affymetrix microarray technique. Confluent preadipocytes from subcutaneous (SC) and omental (OM) adipose tissue collected from five female patients were treated for 24 h with 100 nM cortisol (F), RNA was pooled and hybridised to the Affymetrix U133 microarray set. We identified 72 upregulated and 30 downregulated genes by F in SC cells. In OM preadipocytes, 56 genes were increased and 19 were decreased. Among the most interesting were transcription factors, markers of adipocyte differentiation and glucose metabolism, cell adhesion and growth arrest protein factors involved in G-coupled and Wnt signalling. The Affymetrix data have been confirmed by quantitative real-time PCR for ten specific genes, including HSD11B1, GR, C/EBPalpha, C/EBPbeta, IL-6, FABP4, APOD, IRS2, AGTR1 and GHR. One of the most upregulated genes in OM but not in SC cells was HSD11B1. The GR was similarly expressed and not regulated by glucocorticoids in SC and OM human preadipocytes. C/EBPalpha was expressed in SC preadipocytes and upregulated by F, but was below the detection level in OM cells. C/EBPbeta was highly expressed both in SC and in OM preadipocytes, but was not regulated by F. Our results provide insight into the genes involved in the regulation of adipocyte differentiation by cortisol, highlighting the depot specifically in human adipose tissue.